Prediction of Continuous Rain Disaster in Henan Province Based on Markov Model - Xiaoxiao Zhu; Shuhua Zhang; Bingjun Li (Discrete Dynamics in Nature and Society)
Continuous rain disasters occur frequently, which seriously affect maize yield. However, the research on predicting continuous rain disasters is very limited. Taking the maize in Henan Province as an example, the Markov model is used to predict the occurrence of continuous rain in the middle growth and late growth stages (flowering and filling stages) of 13 cities in Henan Province. The results showed that the maize in Henan Province would suffer from continuous rain disaster in 2020 and 2021. Finally, combined with the prediction results, policy recommendations for maize growth in Henan Province are proposed to ensure stable and high yield of maize.